Determination of Correlation between Diabetes Duration and Coronary Artery Disease Severity in Patients Undergoing Coronary Angiography - Hassan Imam; Faisal Ahmed; Sher Muhammad; Bari Babar; Arshad Ali Shah; Syed Dilbahar Ali Shah; Muhammad Nawaz Lashari (Ukrainian Journal of Cardiovascular Surgery, 2024)
Background. Coronary artery disease (CAD) is caused by atherosclerotic process in coronary arteries. Due to extraordinary risk for atherosclerosis in diabetic patients, it is also counted as a vascular disease. Diabetes mellitus (DM) is a direct major associated risk factor in the development of cardiovascular disease with some studies from high income countries reporting correlation between duration of DM and severity of CAD. However, data from Pakistan is scarce.The aim. To determine the correlation between duration of DM and severity of CAD in patients undergoing coronary angiography at the tertiary care cardiac center.Materials and methods. This cross-sectional study was conducted in the Department of Cardiology, Civil Hospital Karachi, among 160 patients who were scheduled for coronary angiography with comorbid DM. Correlation between duration of DM and severity of CAD (as assessed by the modified Gensini score) was statistically measured and reported employing Pearson’s correlation coefficient (r).Results. Significant correlation between DM duration and total Gensini score was shown with r = 0.759 and p = 0.000001. With the increase in the duration of DM, the severity of CAD also increased.Conclusion. DM duration is positively associated with the modified Gensini score and the significant determinants of CAD severity tend to be relevant.